(3abg GddZI hSQ GdYQHjIs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3QSGdI LYdgG YHO Gdedc GHf eMeO Hf GSeGYjd ebOeI dcJGH abg GddZI hSQ GdYQHjI ef CMH GdQShd GdYQHi CMH GdYQHjI s
(3BNQgG (B:s
(3aUd ai Jbjje GdJeGe hGdceGd gi YTQI cGedI fYeI SGFZI QGYi GdWYGe ef GdQHY hgh GdfRd hGddg GYde s
(3HChdg bQGAIs
(3Cda GdeDda gPG GdcJGH deLdS GdCejQ GdSjO CHj GdaVd YHjO Gddg Hf CMeO GdejcGdis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GddZIs